PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR Go Public (Studi Empiris pada Perusahaan yang Terdaftar di BEI 2011 Sampai 2013) - veno, Andri (Benefit: Jurnal Manajemen dan Bisnis, 2015)
The purpose of this research was to examine the effect of Effect of Good Corporate Governance, which includes: the size of the directors council, commissioner council, the total of commissioner council, and the audit committee of the companys performance. This research used a sample of 48 companies listed on the stock exchanges of Indonesia, by using purposive sampling which publishes financial report for 3 years from 2011-2013. The method analysis of this researchÂ  using multiple regression.Results from this research show that (1) The size of the council of directors significant positive effect to Â the corporate performance , (2) Independent council commissioner wasnâtÂ  significant effect to corporate performance (3) the total of council commissioner wasnât significant effect to corporate performance (4) Audit Committee significant positive effect to Â corporate performance (5) Simultan, Size of the directors council, Independent of the commissioners council, the total of commissioners council and the Audit Committee had a significant effect to the corporate performance.